2021
DOI: 10.1038/s42003-021-01926-4
|View full text |Cite
|
Sign up to set email alerts
|

De novo histidine biosynthesis protects Mycobacterium tuberculosis from host IFN-γ mediated histidine starvation

Abstract: Intracellular pathogens including Mycobacterium tuberculosis (Mtb) have evolved with strategies to uptake amino acids from host cells to fulfil their metabolic requirements. However, Mtb also possesses de novo biosynthesis pathways for all the amino acids. This raises a pertinent question- how does Mtb meet its histidine requirements within an in vivo infection setting? Here, we present a mechanism in which the host, by up-regulating its histidine catabolizing enzymes through interferon gamma (IFN-γ) mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 95 publications
(56 reference statements)
1
24
0
1
Order By: Relevance
“…Although in this study, DLA has not been established as an exclusive inhibitor for IGPD and its antitubercular activity may be contributed by several other targets, it has shown promising inhibition of Mtb IGPD both biochemically and structurally. Notably, a recent study by our group established that an uninterrupted biosynthesis of histidine is essential for Mtb to evade the host immune response and survive; putting an end to the speculations that Mtb could survive by importing histidine from the host if the pathway is blocked 12 . This new knowledge has significantly enhanced the importance of targeting histidine biosynthesis pathway enzymes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although in this study, DLA has not been established as an exclusive inhibitor for IGPD and its antitubercular activity may be contributed by several other targets, it has shown promising inhibition of Mtb IGPD both biochemically and structurally. Notably, a recent study by our group established that an uninterrupted biosynthesis of histidine is essential for Mtb to evade the host immune response and survive; putting an end to the speculations that Mtb could survive by importing histidine from the host if the pathway is blocked 12 . This new knowledge has significantly enhanced the importance of targeting histidine biosynthesis pathway enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…With the emergence of drug‐resistant Mtb strains, 1,2 TB has resurged as a global emergency, which mandates the need to develop novel therapeutic interventions. Among the vast worldwide efforts in this respect, a plethora of studies showed that the disruption of the function of the individual central metabolic pathways, 3 such as thiamine biosynthesis, 4 amino acid biosynthesis, that is, tryptophan, 5,6 leucine, 7 arginine, 8 serine, 9 histidine, 10‐12 and aspartate biosynthesis, 13 represents new strategies to curb Mtb infection. Mtb , unlike humans, can biosynthesize all amino acids 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of M. tuberculosis to NSC369066 inhibited its growth in a bactericidal manner and this was partially restored upon supplementation of medium with L-methionine. Similar supplementation studies have been performed to validate enzymes of other amino acid biosynthetic pathways from M. tuberculosis as drug-targets 31 , 35 , 68 70 . Although, NSC73735 was inactive against M. tuberculosis , it showed good activity against S. aureus in liquid cultures.…”
Section: Discussionmentioning
confidence: 95%
“…Reduced histidine metabolism has been described in chronic inflammatory disease such as systemic lupus erythematosus ( 30 , 31 , 54 ). IFN-γ has also been demonstrated to upregulate the histidine catabolizing enzymes resulting in the depletion of free histidine ( 55 ). Therefore, the correlations between histidine metabolism and two plasma biomarkers essential for T cell activation emphasized the potential inhibitory effect of histidine metabolism in immune activation and IRIS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%